Identification of Coconut Fiber Length on REM Pad Characteristics - Rofiqi, Mochamad; Anas Mukhtar (Journal of Educational Engineering and Environment, 2024)
The need for automotive material products will increase with the increasing variety of types, brands and needs for the number of motorized vehicles in Indonesia. The more uncertain the economic conditions in Indonesia, the higher the drive to produce automotive material products that are economical, of good quality and acceptable to the market, one of which is from coco fiber. This study aims to obtain the effect of the type and ratio of a mixture of coconut coir and aluminum powder on the characteristics of the brake pads. Prior to data collection, the brake pads are affixed to the stamp pad. Data collection was carried out by swiping the test object (brake pads) on sandpaper number 40, 150, and 320. Where the brake pads were loaded with 1 kg. as a result of testing provides that use coconut coir fiber which has more composition results in longer and wider strokes